Morphological affinities of a fossil ulna (KNM-WS 65401) from Buluk, Kenya. Issue 166 (May 2022) - Nishimura, Abigail C.; Russo, Gabrielle A.; Nengo, Isaiah O.; Miller, Ellen R.
Abstract: The morphological affinities of a primate proximal ulna (KNM-WS 65401) recovered from the late Early Miocene site Buluk, Kenya, are appraised. Nineteen three-dimensional landmarks on ulnae from 36 extant anthropoid species ( n = 152 individuals) and KNM-WS 65401, as well as a subset of 14 landmarks on six ulnae belonging to other East African Miocene catarrhine taxa, were collected. To quantify ulnar shape, three-dimensional geometric morphometric techniques were used and linear dimensions commonly cited in the literature were derived from the landmark data. KNM-WS 65401 is situated between monkeys and hominoids in the principal components morphospace. KNM-WS 65401 shares features such as a short olecranon process, broad trochlear notch, and laterally oriented radial notch with extant hominoids, whereas features such as an anteriorly directed trochlear notch and flat, proximodistally elongated, and anteroposteriorly narrow radial notch are shared with extant monkeys. Principal component scores and linear metrics generally align KNM-WS 65401 with both suspensors and arboreal quadrupeds, but quadratic and linear discriminant analyses of principal component score data provide posterior probabilities of 80% and 83%, respectively, for assignment of KNM-WS 65401 to the suspensory group. Compared with fossil ulnae from other Miocene primates, KNM-WS 65401 is morphologically most distinct from KNM-LG 6, attributed to Dendropithecus macinnesi, and morphologically most similar to KNM-WK 16950R, attributed to Turkanapithecus kalakolensis . The KNM-WS 65401 individual likely possessed more enhanced capabilities for elbow joint extension, perhaps during suspensory behaviors, compared with other Miocene primates in the sample.